The novel driver gene ASAP2 is a potential druggable target in pancreatic cancer. Issue 4 (5th March 2021) - Fujii, Atsushi; Masuda, Takaaki; Iwata, Michio; Tobo, Taro; Wakiyama, Hiroaki; Koike, Kensuke; Kosai, Keisuke; Nakano, Takafumi; Kuramitsu, Shotaro; Kitagawa, Akihiro; Sato, Kuniaki; Kouyama, Yuta; et al.
Abstract: Targeting mutated oncogenes is an effective approach for treating cancer. The 4 main driver genes of pancreatic ductal adenocarcinoma (PDAC) are KRAS, TP53, CDKN2A, and SMAD4, collectively called the "big 4" of PDAC, however they remain challenging therapeutic targets. In this study, ArfGAP with SH3 domain, ankyrin repeat and PH domain 2 ( ASAP2 ), one of the ArfGAP family, was identified as a novel driver gene in PDAC. Clinical analysis with PDAC datasets showed that ASAP2 was overexpressed in PDAC cells based on increased DNA copy numbers, and high ASAP2 expression contributed to a poor prognosis in PDAC. The biological roles of ASAP2 were investigated using ASAP2 ‐knockout PDAC cells generated with CRISPR‐Cas9 technology or transfected PDAC cells. In vitro and in vivo analyses showed that ASAP2 promoted tumor growth by facilitating cell cycle progression through phosphorylation of epidermal growth factor receptor (EGFR). A repositioned drug targeting the ASAP2 pathway was identified using a bioinformatics approach. The gene perturbation correlation method showed that niclosamide, an antiparasitic drug, suppressed PDAC growth by inhibition of ASAP2 expression. These data show that ASAP2 is a novel druggable driver gene that activates the EGFR signaling pathway. Furthermore, niclosamide was identified as a repositioned therapeutic agent for PDAC possibly targeting ASAP2. Abstract : In this study, we identified ArfGAP with SH3 domain, ankyrin repeat and PH domain 2 ( ASAP2 ) as a potentially druggable driver gene using bioinformatics analysis in pancreatic ductal adenocarcinoma (PDAC), which is one of the most lethal cancers worldwide. Then, we showed that ASAP2 promoted cell migration and proliferation by facilitating cell cycle progression through phosphorylation of EGFR. Finally, we identified niclosamide, an antiparasitic drug, as a repositioned therapeutic agent for PDAC, possibly targeting ASAP2.